PENERAPAN HUKUM PIDANA PELAKUTINDAK PIDANA PENCUCIAN UANG DALAM TINDAK PIDANA ASAL - Firdaus (2021)
Money laundering is commonly used to describe efforts made by a person or legal entity to legalize "dirty" money, which is obtained from the proceeds of a crime with certain activities such as forming a business, transferring or converting to a bank or foreign exchange as a step to remove the background back from where the money was obtained. The proof of the element of the judge's criminal act is in two options, namely proving the predicate crime first and continued by proving the crime of money laundering as in the Supreme Court Decision Number: 1607 K / PID.SUS / 2012 or only proving the crime of money laundering only in the event that predicate offenses are not charged as in the Decision of PT Makassar Number: 302 / PID.SUS / 2014 / PT.MKS. This raises the problem of differences in handling and obstacles in the application of predicate offenses in proving cases of money laundering. So that proving ML cases should be done cumulatively with predicate crime. And if there is insufficient evidence on predicate crime then it must strengthen the evidence of the existence of ML's crime against wealth with predicate crime. This research is a library research research using qualitative type by reviewing the Supreme Court Decision Number: 1607 K / PID.SUS / 2012 and PT Makassar Decision Number: 302 / PID / 2014 / PT.MKS. From this research it is known that the proof of ML cases in the Supreme Court Decision Number 1607 K / PID.SUS / 2012 is implemented based on Article 75 of the TPPU Law by combining ML and its predicate crimes because sufficient evidence has been found in the original criminal. Meanwhile, the decision of PT Makassar Number 302 / PID.SUS / 2014 / PT.MKS is based on Article 69 of the TPPU Law, which is to separate TPPU from predicate crimes because enough evidence has been found in TPPU, while the original criminal still takes longer to collect evidence. . The obstacle in the application of predicate offenses to proof of ML cases is in proving the elements of assets which are known or reasonably suspected to be originating from the original criminal act.